Risk factors affecting the construction projects in the developing countries - R. A., Bahamid; Doh, Shu Ing; M. A., Al-Sharaf (IOP Publishing, 2019)
This review focused on the identification of critical risk factors that influence the construction projects conducting in the developing countries. In order to attain this goal, a comprehensive literature review on risk management of the construction projects, particularly emphasizing on the developing countries was carried out. The identified risk factors can be a lead to achieve the goals of the project which includes time, cost and quality. This review used specific criteria to extract the risks factors based on the main purpose of the study. A sum total of 111 risk factors were figured out from the previous studies. Based on the criteria used for the classifications, 56 risk factors were observed as the most crucial risk factors influencing the construction projects of developing countries.